TEXTURE AND MECHANICAL BEHAVIOUR OF Ti AND Nb-Ti STABILIZED IF STEELS - Fabio Moreira da Silva Dias; Fabiano Augusto Vallim Fonseca; Christien Guisard Hauegen; Jefferson Fabricio Cardoso Lins; Marcos Flavio de Campos (Tecnologia em Metalurgia, Materiais e Mineração, 2013)
An analysis of the crystallographic texture and mechanical behavior of two types of IF steels is presented. Two steels, Ti and Nb-Ti, were submitted to different thermal annealing cycles in a continuous hot-dip galvanizing line, heat treated at temperatures of 860°C and 760°C. The more relevant characteristics of mechanical properties are evaluated. The crystallographic texture of the samples is determined by electron diffraction technique of back-scattering (SEM-EBSD). The intensity of orientation <111>//ND is evaluated and compared. Metallographic characterization is done, and the ferritic grain size is measured with optical microscopy. The mechanical behavior of materials is characterized in the tensile test with 80 mm gauge length.